Gaming relationship to social psychology and micro-expressions. - Durning, Kiersten (My University, 2016)
With increasing popularity in society, gaming has become a common influence in most individuals' lives. Psychology as a field is generating a demand for research and a better understanding of how gaming has contributed to society with a positive or a negative impact. Social exchange that requires in-person interaction (such as interpreting emotional facial cues) has yet to be explored in the field of psychology in relationship to gaming. The purpose of this study is to determine if a relatively non-social task, such as gaming, can predict a social situation such as reading facial emotions. This study will determine if the amount of time and experience with gaming will influence the individual's ability to read human emotion and micro-expressions accurately. In this study, participants recorded the amount of hours spent gaming, completed a micro-expression eMETT3.0 practice, and the Experiences in Close Relationships attachment scale. Results concluded no relationships were found between gamers and the ability to read micro-expressions compared to non-gamers.
Keywords: Video gamers; Emotion recognition; Facial expression; Gaming; Emotions; Micro-expression; Microexpressions; Micro expressions; Reaction time